1992
DOI: 10.1002/j.1460-2075.1992.tb05437.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical cytoplasmic domains of the common beta subunit of the human GM-CSF, IL-3 and IL-5 receptors for growth signal transduction and tyrosine phosphorylation.

Abstract: The high‐affinity receptors for human granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), interleukin 3 (IL‐3) and interleukin 5 (IL‐5) are composed of two distinct subunits, alpha and beta c. The alpha subunits are specific for each cytokine, whereas the beta subunit (beta c) is shared by the three receptors and is an essential component of signal transduction. We have made a series of mutant beta c cDNAs that delete various regions of the cytoplasmic domain and examined the function of these mutants b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
241
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(256 citation statements)
references
References 58 publications
13
241
0
2
Order By: Relevance
“…We previously reported that interleukin 3 (IL-3) and granulocyte macrophage colony stimulating factor (GM-CSF) stimulate multiple signal transduction pathways through the distinct cytoplasmic domains of the shared signaling receptor (bc) Kinoshita et al, 1995b;Miyajima et al, 1993;Sakamaki et al, 1992;Sato et al, 1993). The membrane-proximal short region (a.a. 455 ± 544) mediates c-myc induction (Kinoshita et al, 1995b;Sato et al, 1993) as well as the activation of the Jak2-Stat5 pathway (Quelle et al, 1994) that leads to the induction of several immediate early genes including pim-1 (Mui et al, 1996), oncostatin M (Yoshimura et al, 1996) and cis (for cytokine-inducible SH2-containing protein) (Yoshimura et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that interleukin 3 (IL-3) and granulocyte macrophage colony stimulating factor (GM-CSF) stimulate multiple signal transduction pathways through the distinct cytoplasmic domains of the shared signaling receptor (bc) Kinoshita et al, 1995b;Miyajima et al, 1993;Sakamaki et al, 1992;Sato et al, 1993). The membrane-proximal short region (a.a. 455 ± 544) mediates c-myc induction (Kinoshita et al, 1995b;Sato et al, 1993) as well as the activation of the Jak2-Stat5 pathway (Quelle et al, 1994) that leads to the induction of several immediate early genes including pim-1 (Mui et al, 1996), oncostatin M (Yoshimura et al, 1996) and cis (for cytokine-inducible SH2-containing protein) (Yoshimura et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The ␣ subunit is specific for each receptor (Gearing et al, 1989), whereas the ␤ subunit (␤c) is shared by all (Kitamura et al, 1991). We reported that IL-3 and GM-CSF stimulate multiple signal transduction pathways through distinct cytoplasmic domains of the ␤c (Sakamaki et al, 1992;Watanabe et al, 1993b). The membrane proximal region, which contains the box1 motif, is involved in the induction of c-myc as well as in cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…This, however, is being challenged by recent reports suggesting its involvement in regulating cell growth (22,23). The ␤ subunit, on the other hand, has a long intracytoplasmic tail and plays a major role in transmitting the signal inside the cell (24). Neither subunit has intrinsic enzymatic activity, nor are they known to link to G proteins directly (19).…”
mentioning
confidence: 99%